Tiller demography of tall fescue and tall wheatgrass cut at different times during the reproductive phase - Scheneiter, Jorge Omar (2023)
Background: Tall fescue (TF) and tall wheatgrass (TW) are the main temperate perennial grasses used for livestock grazing in the Pampas region of Argentina. In this region, pastures based on these grasses show low tiller density and the presence of bare soil in winter. Methods: An experiment was performed in pots kept outdoors. Plants of TF and TW were cut every 550°C day and 700°C day, respectively. In each species, reproductive tillers were removed at different times: (i) at each cut, (ii) when they reached the flag leaf stage, or (iii) when they reached full bloom. Tiller appearance, tiller death, and type of bud (basal or axillary) of the tillers present were determined. Results: Tiller appearance decreased from July to April. Minimum values were 0.2 and 1.1 tillers 100 tillers−1 day−1 in TF and TW, respectively. In TF, tiller death began in September–October and increased from 0.2 to 0.8 tillers 100 tillers−1 day−1 in March–April. In TW, tiller death began in October–November and increased from 0.6 to 0.8–1.0 tillers 100 tillers−1 day−1 from February to April. Conclusions: Defoliation of reproductive tillers affected the tiller density of TF plants in spring and in the following fall. In TW, the treatments did not modify the tiller density of the plants.